Decisions of the Chief Pharmaceutical Inspector on Medicinal Product Advertising in Terms of a Health Care Measure. Between Freedom of Expression, Freedom of Economic Activity and Responsibility for Health - Jaskuła, Lidia K. (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
The concern for human health is one of the tasks of public administration in its mission for the sake of the common good. The body entrusted with some of the tasks in this field is the Chief Pharmaceutical Inspector/Główny Inspektor Farmaceutyczny (GIF). The aim of this paper is to examine whether the statutory power to issue administrative decisions, within the field of medicinal product advertising, granted to the Chief Pharmaceutical Inspector, constitutes a measure of health care and whether it is an effective measure at all. The main issue that the article addresses has been contained in the question ”Do the decisions of the Chief Pharmaceutical Inspector, regarding medicinal product advertising, constitute an effective measure of health care?”. Analyses carried out within the framework of the study have led to the conclusion that the Chief Pharmaceutical Inspector, acting within its competences, exercising supervision in the field of advertising, interferes with two constitutional freedoms that are essential for a democratic state ruled by law: freedom of speech and freedom of economic activity. However, it does it in order to protect the special value of health. Thus, the Chief Pharmaceutical Inspector’s practice in terms of resolving matters in this area is a balancing act between freedom of expression, freedom of economic activity and responsibility for health. Unfortunately, this practice raises many concerns. Although the decisions of the Chief Pharmaceutical Inspector regarding medicinal product advertising constitute a measure of health care, they are ineffective in practice and the society is subjected to persuasive messages regarding medicinal products which very often clearly violate the provisions of the Pharmaceutical Law Act.